Contributions of Adaptive Plant Architecture to Transgressive Salinity Tolerance in Recombinant Inbred Lines of Rice: Molecular Mechanisms Based on Transcriptional Networks - Pabuayon, Isaiah Catalino M.; Kitazumi, Ai; Gregorio, Glenn B.; Singh, Rakesh Kumar; de los Reyes, Benildo G. (Frontiers in Genetics, 2020)
Genetic novelties are important nucleators of adaptive speciation. Transgressive segregation is a major mechanism that creates genetic novelties with morphological and developmental attributes that confer adaptive advantages under certain environments. This study examined the morpho-developmental and physiological profiles of recombinant inbred lines (RILs) from the salt-sensitive IR29 and salt-tolerant Pokkali rice, representing the total range of salt tolerance including outliers at both ends of the spectrum. Morpho-developmental and physiological profiles were integrated with a hypothesis-driven interrogation of mRNA and miRNA transcriptomes to uncover the critical genetic networks that have been rewired for novel adaptive architecture. The transgressive super-tolerant FL510 had a characteristic small tiller angle and wider, more erect, sturdier, and darker green leaves. This unique morphology resulted in lower transpiration rate, which also conferred a special ability to retain water more efficiently for osmotic avoidance. The unique ability for water retention conferred by such adaptive morphology appeared to enhance the efficacy of defenses mediated by Na+ exclusion mechanism (SalTol-effects) inherited from Pokkali. The super-tolerant FL510 and super-sensitive FL499 had the smallest proportions of differentially expressed genes with little overlaps. Genes that were steadily upregulated in FL510 comprised a putative cytokinin-regulated genetic network that appeared to maintain robust growth under salt stress through well-orchestrated cell wall biogenesis and cell expansion, likely through major regulatory (OsRR23, OsHK5) and biosynthetic (OsIPT9) genes in the cytokinin signaling pathway. Meanwhile, a constitutively expressed cluster in FL510 prominently featured two transcription factors (OsIBH1, TAC3) that control tiller angle and growth habit through the brassinosteroid signaling pathway. Both the putative cytokinin-mediated and brassinosteroid-mediated clusters appeared to function as highly coordinated network synergies in FL510. In contrast, both networks appeared to be sub-optimal and inferior in the other RILs and parents as they were disjointed and highly fragmented. Transgressively expressed miRNAs (miR169, miR397, miR827) were also identified as prominent signatures of FL510, with functional implications to mechanisms that support robust growth, homeostasis, and osmotic stress avoidance. Results of this study demonstrate how genetic recombination creates novel morphology that complements inducible defenses hence transgressive adaptive phenotypes.